THE STRUCTURE OF THE INFORMATION-ANALYTICAL SPACEINNOVATION CORPORATION - Olga B. Emelyanova (Статистика и экономика)
In article is highlighted the components of information space of innovative corporations, and is offered a set-theoretic description of the requirements to information and analytical support. It description allows formalize the formulation and subsequent solution of problem justify of factors the effective use of information and analytical support innovation activities of the corporation.